Cybaeus (Araneae: Cybaeidae): the consocius species group of the Californian clade - Bennett, Robb; Copley, Claudia; Copley, Darren (Zootaxa, 2021)
Species of North American Cybaeus L. Koch (Araneae: RTA clade: Cybaeidae) are common moist-forest spiders classified in Holarctic and Californian clades. Here, in the third paper in a planned series reviewing the six Californian clade species groups, we review the species of the consocius group. We recognize nine species: Cybaeus consocius Chamberlin & Ivie, C. hesper Chamberlin & Ivie, C. hummeli Bennett spec. nov., C. opulentus spec. nov., C. pan Bennett spec. nov., C. penedentatus Bennett, C. simplex Roth, C. ubicki Bennett spec. nov., and C. vulpinus Bennett. Eight of these species have restricted distributions in the central Sierra Nevada Mountains of eastern California, U.S.A (C. opulentus, C. pan spec. nov., and C. vulpinus) or the central coast of western California (C. consocius, C. hesper, C. hummeli spec. nov., C. penedentatus, and C. ubicki spec. nov.); a single species (C. simplex), is relatively widely distributed in western Oregon, U.S.A. Descriptions, illustrations, distribution maps, and an identification key are provided as well as a discussion of conservation issues of relevance to the group.